Humanitarian Activities of Medecins Sans Frontieres (MSF) in Some Selected Sub-Saharan African Countries - Akinga, Anna Yonnana; Oriaku, Bismack Chisom (NIU Journal of Social Sciences, 2023)
This paper examines the humanitarian activities of Medecins Sans Frontieres (MSF), also known as Doctors Without Borders, in some selected Sub-Saharan African countries; Somalia, Rwanda, Sudan, Liberia and Nigeria. MSF is an international non-governmental organization (NGO) that provides medical assistance to populations affected by crises, including armed conflicts, epidemics, and natural disasters. This paper explores the historical context, principles, and operational strategies of MSF in delivering humanitarian aid. The paper adopted descriptive analytic method and secondary source of data was mostly used in the course of writing this paper. The findings of this paper reveals that the MSF has contributed immensely in providing emergency medical assistance in situations of armed conflicts. The paper also reveals that the MSF also faces some obstacles that impact their ability to deliver medical care to affected communities. Some of the key challenges identified included; insecurity, limited resources and funding among others. The paper therefore recommends that the leadership and members of MSF should endeavour to be as neutral as possible in political and ideological matters because how the organization is viewed would determine whether it will be granted access into troubled areas to carry out its humanitarian objectives. Keywords: Conflict, International Humanitarian Law, Medical Humanitarianism, Medecins Sans Frontieres, Sub-Saharan Africa.